2022
DOI: 10.1155/2022/1511479
|View full text |Cite
|
Sign up to set email alerts
|

International Gold Price Forecast Based on CEEMDAN and Support Vector Regression with Grey Wolf Algorithm

Abstract: Considering the complexity pattern of the gold price, this paper adopts the decomposition-reconstruction-forecast-mergence scheme to perform the international gold price forecast. The original gold price data are decomposed into 12 intrinsic mode functions and a residual by the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method, and then the 13 sequences are reconstructed into a high-frequency subsequence (IMFH), a low-frequency subsequence (IMFL), and the residual (Res). Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Researchers reported that Bi-LSTM Network outperformed other networks such as LSTM, CNN-LSTM, and CNN-Bi-LSTM. Lu et al [ 25 ] predicted the gold price using a hybrid model called complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN)- grey wolf optimizer (GWO)- SVR and high-frequency intrinsic mode functions subsequence (IMFH), low-frequency intrinsic mode functions subsequence (IMFL), and the residual as input data. The IMFL and the residual have higher correlations compared to IMFH.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers reported that Bi-LSTM Network outperformed other networks such as LSTM, CNN-LSTM, and CNN-Bi-LSTM. Lu et al [ 25 ] predicted the gold price using a hybrid model called complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN)- grey wolf optimizer (GWO)- SVR and high-frequency intrinsic mode functions subsequence (IMFH), low-frequency intrinsic mode functions subsequence (IMFL), and the residual as input data. The IMFL and the residual have higher correlations compared to IMFH.…”
Section: Related Workmentioning
confidence: 99%
“…The forecasting performance of SVR is mainly affected by C and gamma (Ngo N et al, 2022), so we used optimization algorithms to optimize these two parameters. Based on previous literature and the performance of the three optimization algorithms in this paper, for fairness, we have the same settings for all three algorithms (Lu et al, 2022;Mohammed S et al, 2022;Sharma and Shekhawat et al, 2022;Su X et al, 2022): iterations: 30; population: 20; and lower and upper bound [0.1,1]. In the Bagging algorithm, the main factors that affect its performance include base learners and data samples (Mohammed and Kora et al, 2023).…”
Section: Parameter Settingmentioning
confidence: 99%
“…Additionally, accurate forecasting of gold prices can benefit commodity markets and the global economy. Predicting gold prices' volatility more precisely allows market participants to make better-informed decisions regarding their investments in gold [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%